The Relationships between Motivation Type and Elective Sports Participation among Sport Science Undergraduate Students of Wolaita Sodo University - Tesfaye Diro, Debrework (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2020)
The major objective of this study was to find out the motivational difference between football, volleyball, basketball, handball and athletics sport elective students. This research followed cross sectional survey study design with purposive sampling technique. The Sport Motivation Scale was used to gather data on the motivation for sport participation. Data analysis was conducted by SPSS Version 22. One-way ANOVA was computed to analyze the differences among elective sport means with manually calculated effect size and Tukey HSD post hoc was conducted to determine which groups differ from each other. The age ranges of the students were 19 to 25 with a mean age of 22.05 ± 1.43 years old. There were 67 % female and 33 % male respondents. The majority of the students was assigned to their respective elective sport of their choice which accounts about 77 % and the rest 23 % were assigned to their second-choice elective sport. Of the students participated in the study, 16 (21%) identified as volleyball elective students, followed by 16 (21%) athletics elective students, 15 (20%) football elective students 14 (19%) basketball and 14 (19%) handball elective students. ANOVA analysis revealed that there was statistically significant difference between elective sport students (F 4, 70=51.30, P<0.001, η2= 0.74) that football sport elective students are significantly intrinsically motivated than basketball (p<0.001), handball (p<0.001) and athletics (p<0.001) sport elective students. The extrinsic motivation was also found significant (F 4, 70=56.18, p<0.001, η2= 0.76). The extrinsic motivation mean score of football elective sport students was significantly higher than basketball (p<0.001), handball (p<0.001) and athletics (p<0.001) elective sport students. Post hoc test showed that handball elective students amotivation mean score was significantly higher than football (p<0.001), volleyball (p<0.001), basketball (p<0.001) and athletics (p<0.001) elective students. Female students amotivation mean value was (M =16.62, SD =4.11) significantly higher than the mean score of male students (M = 13.96, SD= 4.08) at (t (73) =1.02, p =0.01).There was positive relationship between the mean score of intrinsic motivation and extrinsic motivation, (r=0. 822, p <0. 001). Negative correlation was found between intrinsic and amotivation (r=-0.764, p <0. 001) and extrinsic and amotivation (r=-0.762, p<0. 001). Generally, this study found that football elective students have higher intrinsic and extrinsic motivation followed by basketball elective students. Female students tend to be highly amotivated than male students